Isolated renal mucormycosis in children: A case report and review of the literature - Sachit Anand; Deepika Kainth; Anjan Kumar Dhua; Mehak Sehgal; Minu Bajpai; Prasenjit Das; Devasenathipathy Kandasamy (Wolters Kluwer Medknow Publications, 2021)
Isolated renal mucormycosis is rare in children. A case of 3-month-old infant presenting with right-sided flank lump and fever is being reported. Investigations revealed a nonfunctioning right kidney with intrarenal abscesses and a low percent-frequency of T-cells. He made an uneventful recovery following surgery and systemic antifungal therapy. Compared to the other forms of deep mucormycosis, a review of literature suggests favorable prognosis in children with isolated renal involvement.